The curriculum of primary public education in the Empire: girls in the province of Rio Grande do Norte (Research, Society and Development, 2018)
The main instruction for girls in elementary schools in the province of Rio Grande do Norte is during the Brazilian Empire. It was problematic: what is the curriculum that pedagogical practices aimed at the learning of girls in this context? The proposal was the subject in instructional and the expectations for learning for girls works in legislations for Rio Grande d. The period delimited for the study (1822-1889) includes the formation of the Brazilian national state and the creation of a judicial information system for a new nation that continues being a slave society and with a public education that reaches a minority. The scope of prayer, the orientation and analysis of the devices that guide the rigging of the North-Great School, considering the nature and intentionality of educational legislation. The foundation was based on the approaches of Augusto Tavares de Lyra (2008), Luís da Câmara Cascudo (1955), Jacques Le Goff (1994), Leslie Maria José da Silva Rama (1987) and Maria Inês Sucupira Stamatto (1996) and (2012) about how perceptions of History, education and education laws of Rio Grande do Sul. Indifference to elementary education is fundamental, including for the teaching of household tasks and the limitation of the teaching of Arithmetic. The bases for creating dialog boxes, for both sexes, were created and were not created by the Empire.